(untitled) (PUBMET, 2023)
To ensure the success of Open Science, we have to understand how it systematically changes the research system as a whole. This presentation focuses on the synthesis of the changing research landscape and the utilisation of policies, emerging tools, and practices into shaping end-to-end systems for embedding actionability in all research stages: planning, tracking, and assessing. Specifically, it will explore the designing of interconnected systems that involve Data Management Plans, Scientific Knowledge Graphs, and FAIR Assessors, all of which are essential components of research workflows.